Characterization of the complete plastome of Dysphania botrys, a candidate plant for cancer treatment. Issue 2 (3rd July 2018) - Chen, Yao; Yang, Zhaoping
Abstract: Dysphania botrys belongs to Amaranthaceae and distributes in North Europe, Asia, and North America. It is a medicinal plant with diuretic, antispasmodic, carminative, antidiarrhoeic properties, and a candidate plant for cancer treatment. However, few studies focused on its phylogeny, and its taxonomic status is still controversial. To better understand the evolution of this species, the complete plastome of D. botrys was obtained by next-generation sequencing. It is the first plastome to be sequenced and reported in the genus Dysphania . The plastome is 152, 055 bp in length, which consists of a large single-copy region (LSC, 83, 769 bp; GC content: 34.7%), a small single-copy region (SSC, 17, 916 bp; GC content: 30.1%), and a pair of inverted repeat regions (IRs, 25, 185 bp; GC content: 42.7%). It harbors 112 unique genes, including 78 protein-coding genes, 30 transfer RNA genes, and four ribosomal RNA genes with an overall G + C content of 36.8%. The phylogeny of Amaranthaceae based on the complete plastome sequences of 13 taxa showed that D. botrys belong to subfamily Chenopodioideae. Chenopodioideae, together with Betoideae formed a sister clade to the three subfamilies (Salicornioideae, Suaedoideae, and Salsoloideae), and this sister clade formed an evolutionary sister clade to Amaranthoideae. Our data will largely enrich the genetic information of Dysphania botrys and facilitate future studies on its evolutionary status.